(untitled) (Journal of Music Research Online, 2022)
Since the 1990s, three discrete groups of aficionados have contributed to an insatiable demand for didjeridus (didgeridoos) in Australia and abroad, prompting environmental stewards (a fourth contesting camp) to promote responsible manufacture and trade to combat forest clear-felling and oversupplies of ersatz (inferior) didjeridus. A critical examination of the sourcing and construction of didjeridus harvested in the Top End of the Northern Territory and the Goldfields and Mid West Regions of Western Australia compares the effectiveness of licensing operative in these two states to regulate stem harvesting. In view of a second, more long-term concern — based on scientific prediction that some species of the hitherto adaptable genus, Eucalyptus, will succumb to global warming — the factoring of climate change into the sustainability equation flags future patterns of change in the instrument’s material use and sonic production. Western Australian musician Mark Cain has explored novel ways of making and playing didjeridus. But can alternative materials satisfactorily replace rich eucalypt sonorities? Could the didjeridu — as a symbol of ‘dos’ and ‘don’ts’ — become a vital emblem for the conservation of natural ecosystems?